Correlation of multiparametric MRI (PIRADS grading) and apparent diffusion coefficient values in prostate tumor with Gleason score - Saini, Ravina; Vohra, Aditi; Jain, Amit; Narula, Harneet; Kadyan, Harneet; Singh, Sanjay (Asian Journal of Medical Sciences, 2023)
Background: Multiparametric magnetic resonance imaging (mpMRI) of prostate is the radiological investigation of choice for the evaluation of prostatic tumors. Aims and Objectives: The aim of the present study was to evaluate the efficacy of mpMRI using PIRADS 2.1 grading and apparent diffusion coefficient (ADC) values as a non-invasive investigation in the detection of prostatic tumors and to correlate PIRADS grade and ADC values with Gleason score of prostate cancer (prostate Ca). Materials and Methods: Fifty patients above the age of 50 years presenting with signs and symptoms of prostate Ca were enrolled for the study. All patients were subjected to the mpMRI including ADC values and then all underwent transrectal ultrasound-guided biopsies. The post-biopsy Gleason score was correlated with PIRADS grading and ADC values followed by statistical correlation. Results: There was a positive linear association between PIRADS score and serum prostate-specific antigen levels (+0.433) and inverse relationship between mean tumor ADC values and Gleason score with correlation coefficient of −0.846 (P<0.001). There was a positive linear association between the PI-RADS score and Gleason score (correlation coefficient of +0.739 with P<0.001). In addition, the positive predictive value of mpMRI was 78.79%, while the negative predictive value was 84.34%. Conclusion: Our study concludes that mpMRI with PIRADS grading including ADC values assists in targeting the appropriate biopsy site for better characterization of the prostate Ca as it correlates well with the Gleason score.